2018
DOI: 10.3390/molecules23061482
|View full text |Cite
|
Sign up to set email alerts
|

Compound K Induces Endoplasmic Reticulum Stress and Apoptosis in Human Liver Cancer Cells by Regulating STAT3

Abstract: The ginsenoside compound K (20-O-β-d-glucopyranosyl-20(S)-protopanaxadiol; CK) is an intestinal bacterial metabolite of ginseng protopanaxadiol saponin that has been reported to induce apoptosis in many cancer cells; however, the precise mechanisms of its activity in human hepatocellular carcinoma (HCC) cells remain unclear. Herein, we demonstrated that CK inhibited the growth and colony formation of HepG2 and SMMC-7721 cells, phenotypes that were mediated by inducing apoptosis. Meanwhile, CK showed lower toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
1
37
1
Order By: Relevance
“…Furthermore, a substantial reduction in tumor proliferation was observed in the CK-supplemented mice group [ 84 ]. Also, CK induced apoptosis and ERS in liver cancer cells and xenografted mice by modulating signal transducers and activators of transcription-3 (STAT3) activation [ 85 ]. Another study showed for the first time that CK targeted annexin A2, which leads to inhibition of NF-κB [ 86 ].…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…Furthermore, a substantial reduction in tumor proliferation was observed in the CK-supplemented mice group [ 84 ]. Also, CK induced apoptosis and ERS in liver cancer cells and xenografted mice by modulating signal transducers and activators of transcription-3 (STAT3) activation [ 85 ]. Another study showed for the first time that CK targeted annexin A2, which leads to inhibition of NF-κB [ 86 ].…”
Section: Health-promoting Activitiesmentioning
confidence: 99%
“…There have been a large number of studies investigating the pharmacological effect of ginseng and ginsenosides and the underlying molecular mechanisms. Ginseng and ginsenosides have been reported to play critical roles in preventing and treating many human diseases, including cancers and neuronal, cardiovascular, inflammatory, and metabolic diseases [6], [7], [8], [9], [10]; furthermore, the molecular mechanisms of their pharmacological actions are due to the diverse biological activities of the natural products, such as proapoptosis, antiangiogenesis, stimulation of the central nervous system, antiinflammatory responses, protective effects on DNA, and chemoprophylaxis [6], [9], [17], [18], [19], [20], [21].…”
Section: Ginseng and Ginsenosidesmentioning
confidence: 99%
“… 2019 ; Zhang et al. 2018 ). Ginsenoside compound K (CK) comes from the degradation of products of natural diol-type ginsenosides (Rb1, Rb2 and Rc) in the human intestinal tract, and is the main form of ginsenoside absorption and activity in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng has been used as medicine and health food for a long time. A large number of studies have found that ginsenosides play a pharmacological role in immune regulation, antiinflammation, antioxidation and antitumor (Zeng et al 2018;Jung et al 2019;Zhang et al 2018). Ginsenoside compound K (CK) comes from the degradation of products of natural dioltype ginsenosides (Rb1, Rb2 and Rc) in the human intestinal tract, and is the main form of ginsenoside absorption and activity in vivo.…”
Section: Introductionmentioning
confidence: 99%